(3NhGU GdCZPjI hGdHbhd hGdahGcg hGddMhe hGdCdHGf hCYVGA GdMjhGf hGdGHGQjR hGdCaGhjgs - (3jhMfG Hf eGShjg, CHh RcQjG,J (B243 (3g` s
(3ChdgG (B:s
(3GdMfWI(B: (3Efg djS aj LejY GdMHhH CMSf edGAeI HMQGQJg efgG, hGdOdjd Ydi Pdc eG JYedg ai JaJjM GdNQGLGJ , hZPGDgG CMSf ef LejY GdMHhH s
(3BNQgG (B:s
(3hNGUI GdCjfShf, jfaY ef YSQ GdHhd hEeJfGYg , hNGUI GdcQaS jfaY ef GdaVhd GdZdjXI s
(3Vef eLehY s
(3GfXQg eY GdWH GdbTJGdi (B- (3fSNI eOQjO Qbe (B"581"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B263s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B87 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdhWfjI HeOQjO (B(7/5240) s
Keywords: (3GdWHs